Pattern of Farmers’ Participation: Lessons from Pump Irrigation Project - Gelar Satya Budhi; Mimin Aminah (Analisis Kebijakan Pertanian, 2009)
Objective of the paper is to describe and analyze the pattern of farmers’ participation during the preparation, physical construction, and maintenance (payment of irrigation service fee) phases.  Emphasis of the discussion will be on the changes in farmers’ participation level during the project implementation.  This paper was based on a research in a pump irrigation project carried out in the Villages of Haurgeulis, Kertanegara, and Wanakaya, Haurgeulis District, Indramayu Regency,WestJavaProvince.  Such pump irrigation was one of participatory project in which beneficiaries are involved during the project execution since planning through maintenance.  Experience of the project implementation suggested that boosting farmers’ participation was a complicated work which needs intensive, long-time, and patient efforts.  During the preparation phase, farmers were actively involved in the project.  This was encouraged by the initiative coming from within of the community, but farmers’ spirit to participate in the project slightly declined up to the start of physical construction.  Fluctuation of farmers’ participation happened in the period of physical construction. Therefore, encouraging measures were applied when the farmers’ participation was going down.  Similar pattern of farmers’ participation also occurred during the maintenance phase, at which farmers found themselves reluctant at initial fee payment. After a sequence of encouragement, the farmers were finally able to operate the pump continuously.